Cooperative Institutional Research Program (CIRP) (United States): Freshman Survey, 1982 ([Verlag nicht ermittelbar], 2002)
The principal purposes of this national longitudinal study of the higher education system in the United States are to describe the characteristics of new college freshmen and to explore the effects of college on students. For each wave of this survey, each student completes a questionnaire during freshman orientation or registration that asks for information on academic skills and preparation, high school activities and experiences, educational and career plans, majors and careers, student values, and financing college. Other questions elicit demographic information, including sex, age, parental education and occupation, household income, race, religious preference, and state of birth. Specific questions asked of respondents in the 1982 survey pertained to PELL Grants and Guaranteed Student Loans (GSL), parents' status (full-time, part-time, lived stogether), whether students lived with their parents for more than two weeks of the year, whether students were listed as dependents on their parents' tax returns, and whether students received assistance worth USD600 or more.